2019
DOI: 10.3389/fphys.2019.00837
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Exercise Concepts for Lumbopelvic and Spinal Muscles – Transferability to Microgravity

Abstract: Low back pain (LBP) is the leading cause of disability worldwide. Over the last three decades, changes to key recommendations in clinical practice guidelines for management of LBP have placed greater emphasis on self-management and utilization of exercise programs targeting improvements in function. Recommendations have also suggested that physical treatments for persistent LBP should be tailored to the individual. This mini review will draw parallels between changes, which occur to the neuromuscular system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 72 publications
(110 reference statements)
1
10
0
Order By: Relevance
“…Among those deteriorations, flattening of spinal curvature and atrophy of lumbar musculature have been documented in astronauts (4). Understanding the effects of prolonged axial unloading on the spinal curvature and lumbar musculature can provide unique information that could be used to design interventions not only for space missions but also for people with low back pain on Earth (28), which is the leading cause of disability worldwide (26).…”
Section: Introductionmentioning
confidence: 99%
“…Among those deteriorations, flattening of spinal curvature and atrophy of lumbar musculature have been documented in astronauts (4). Understanding the effects of prolonged axial unloading on the spinal curvature and lumbar musculature can provide unique information that could be used to design interventions not only for space missions but also for people with low back pain on Earth (28), which is the leading cause of disability worldwide (26).…”
Section: Introductionmentioning
confidence: 99%
“…Given that changes commonly occur in the trunk muscles of people with LBP (for review see (Hides, Hodges, & Lambrecht, 2019)), and the known biomechanical role of muscles such as the MF and LES in controlling segmental (rotational and translational) motion of individual vertebrae, there is a gap in the literature regarding the potential relationship between changes in trunk muscles and in vivo intervertebral motion during flexion and extension of the spine. A recent systematic review examined interactions between passive structures, muscles, and the neural control system, and concluded that there is a lack of studies investigating multiple systems at an intersegmental level (Du Rose, 2018).…”
mentioning
confidence: 99%
“…Furthermore, PA also prevents the formation of fibrosis in muscle tissue and has a role to play in promoting the anti-inflammatory properties of macrophages, reducing tissue sensitivity and metabolism. Use of PA also has a positive impact on myofascial tissue and supports the concept of "physical activity as medicine" [10]. Mora and Valencia [11] believe that for PA to have optimum health benefits in older adults, it must consist of aerobic, strength, flexibility and proprioceptive exercises.…”
Section: Introductionmentioning
confidence: 79%